(untitled) (Research, Society and Development, 2024)
Reactive oxygen species (ROS) are part of the normal metabolism of living organisms. They affect the performance of biological systems, even resulting in the development of diseases. Eliminating ROS represents an effective strategy for preventing diseases. In turn, antioxidants are chemical substances that reduce ROS. They can be synthetic or from natural sources. Unlike synthetic antioxidants, natural antioxidants usually do not have side effects. In this sense, levan is a fructose polysaccharide obtained naturally from plants and microorganisms. Its biological properties mainly include anticancer, anti-inflammatory and antioxidant activities. Currently, levan has received special attention from the point of view of its antioxidant activities. Therefore, the objective of this work was to review the potential of the biopolymer levan as na antioxidant agent. This is na integrative literature review, in which the data found was analyzed using the Content Analysis technique. The results of this investigation showed that its antioxidant action depends on a combination of factors, such as microbial origin, molecular weight, type of assay Applied and polymer concentration. Analysis of the results suggests that levan is na excellent ROS scavenger and can combat pathologies associated with oxidative stress.